Analyzing Tourism Brand Loyalty and E-Marketing Development in Bali, Indonesia - I Made Bayu Wisnawa; I Nengah Subadra; I Wayan Kartimin; I Nengah Aristana; I Wayan Arsawan; Ni Made Hartini (Qubahan Academic Journal)
This study is aimed at determining the factors that lead to long-term brand loyalty among tourists visiting tourist destinations and the effectiveness of e-marketing measures in developing tourism in Bali. It specifically looked at four aspects, including service quality, brand image, brand awareness, and customer satisfaction to determine which was the most important to the tourists. This study adopts a mixed-method approach, primarily using quantitative methods supported by qualitative research to obtain a better understanding of the case. It involved 200 tourists who had visited Bali twice or more. The quantitative data were analyzed using structural equation modeling (SEM) analysis and the qualitative data were analyzed using thematic analysis. The research findings revealed that brand loyalty is formed by brand image, service quality, brand awareness, and customer satisfaction, with customer satisfaction being the strongest factor, while brand image and service quality are less likely to be considered, and the development of e-marketing using popular social media and an integrated web is required to expand the target market.